Effect of plant growth-promoting rhizobacteria inoculation on tomato under commercial shade-house conditions - Palacio-Rodríguez, Rubén; Nava-Reyes, Benjamín; Sánchez-Galván, Homero; Quezada-Rivera, Jesús Josafath; Sáenz-Mata, Jorge (Revista Mexicana de Ciencias Agrícolas, 2022)
In the present study, the effect of the inoculation of Plant Growth Promoting Rhizobacteria (root-dwelling bacteria that promote plant growth through various mechanisms, commonly known by the acronym PGPR); LBEndo1 (Bacillus paralicheniformis), NFbEndo2M2 (Acinetobacter guillouiae), KBEndo3 (Aeromonas caviae), and KBEcto4 (Pseudomonas lini) were evaluated in tomato plants (Solanum lycopersicum L. cv ‘Top1182’) into two soil preparations and the use of compost under commercial shade house conditions. Root weight of tomato plant were increased significantly by inoculation with LBEndo1 and KBEcto4 strains, 119.3 and 81.9%, respectively, on composted flatted soil conditions compared to tomato plants control uninoculated. The PGPR treatments also increased fruit number per plant on both soil condition preparations. KBEcto4 was the treatment with the highest number of fruits with 23 tomatoes plant-1, compared with 18.6 fruits plant-1 control uninoculated on composted flatted soil conditions. The yield and marketable yields were also enhanced by the inoculation of LBEndo1 and KBEcto4 strains in both soil preparations. The plant growth promoting rhizobacteria and the use of organic fertilizer have the potential to be useful under shade house production and is a viable alternative to improving the yield of tomato.
Keywords: compost; PGPR; protected cultivation; tomato; yield